(untitled) (Fiep Bulletin - online, 2014)
Orthorexia consists of a excessive worry for food or healthy food, leading to a very restrictive diet, geared mainly to healthy, natural or organic foods. However, this preoccupation with the "quality" of the food ends up generating physiological, psychological and social consequences. In this context, this article aims to characterize orthorexia, from the discussion of its social aspects, covering the topics: definition, clinical characteristics, diagnostic criteria, risk groups, factors that influence the disorder, cultural and social implications for individuals.